Investigation of deoxidation of high-silicon austenitic sulfuric acid-resistant stainless steel - Dou, Guanxiong; Guo, Hanjie; Guo, Jing; Li, Shaoying; Yan, Yan; Wang, Zihan (Frontiers in Materials, 2022)
The oxygen content in high-Si austenitic sulfuric acid-resistant stainless steels is one of the most detrimental parameters to their corrosion resistance. Based on the ion-molecular coexistence theory (IMCT), a thermodynamic model of the slag-steel reaction of 5% Si austenitic stainless steel with CaF2-CaO-Al2O3-MgO-SiO2 pentabasic slag was developed to investigate the deoxygenation reaction and the oxygen control mechanism of the steel. The model was validated through experiments proposed in this study. The results of the slag-steel reaction during the refining of 5% Si austenitic stainless steel with CaF2-CaO-Al2O3-MgO-SiO2 pentabasic slag indicated that the equilibrium oxygen content was ascertained by the greater of two factors: w[O]%, Si obtained from the [Si]-[O] equilibrium reaction controlled by the activity of SiO2 and w[O]%, Al obtained from the [Al]-[O] equilibrium reaction controlled by the activity of Al2O3. The system temperature and the basicity of slag are the most crucial among the multiple variables affecting the equilibrium oxygen content. However, when the basicity of the slag is less than 2, the oxygen content in steel is controlled by the w[O]%, Si obtained from the [Si]-[O] equilibrium reaction, which is controlled by the activity of SiO2. When the basicity of the slag is greater than 2, nevertheless, the oxygen content is controlled by a variety of factors within the slag composition. Thus, achieving ultra-low oxygen steel necessitates not only a basicity of slag greater than 2, but also the activity of Al2O3. When the Al2O3 content varies between 0% and 10% at 1873 K with basicity of 2.0, the total oxygen content of austenitic stainless steel with 5% Si is less than 7 ppm. The total oxygen content in steel can reach a minimum value of 3.4 ppm when the slag composition encompasses w(CaF2)%=29.38, w(CaO)%=44.07, w(SiO2)%=14.69, w(MgO)%=9.89, w(Al2O3)%=1.96. The high basicity of slag reduces the total oxygen content of stainless steel, whereas the influence of redox reactions between Si and Al results in a higher Al content in steel and the formation of more inclusions during solidification. Thus, the optimal Al2O3 content is less than 4% and the optimal basicity is 2.4 during the refining process.